The Role of Artificial Intelligence in Advancing Inclusive Education: Opportunities and Challenges - Gabriel Julien (Language, Literature and Education: Research Updates Vol. 5, 2025)
It is an undisputed fact that artificial intelligence (AI) is extensively used in the field of education and offers numerous opportunities in teaching and learning. For example, it is used to impart knowledge, stimulate comprehension, and heighten intelligence. Moreover, it is treasured as a substantial support in teaching and learning. It is also instrumental in empowering and inspiring students. Artificial Intelligence allows computer systems and machines to perform tasks that typically require human intelligence. Some of these include problem-solving and decision-making. Hence, it can learn from data and augment its performance over time and is instrumental in addressing complex scenarios by identifying patterns and making predictions. It can also make decisions based on available data and pre-programmed logic. The emergence of AI also has a positive impact on inclusive education. The general concept of inclusive education ensures that all students, regardless of background, learning abilities, or disabilities, have equal access to quality educational opportunities. It is basically concerned about creating proper learning environments where everyone feels welcome, valued, and supported, allowing them to participate and thrive in their own unique ways. Since these technologies can potentially transform teaching and learning, it is important to understand how they can be used to further advance inclusive education. Some of the challenges with AI are the lack of diversity and representation in the development and deployment of AI systems. This can lead to biased AI models that perpetuate existing social inequalities and exclude certain groups of people from benefits and opportunities. This literature-based research analysed some advantages and challenges of incorporating AI in teaching and learning and highlighted how it influences inclusion. Based on the literature, some of the advantages of AI are improved performance of students, motivation, and encouragement of students. This review also identified some challenges associated with the use of AI for inclusive education, such as technological difficulties, poor connectivity, pedagogical issues, and limitations of the database. Some recommendations are proposed to address these challenges. This research can assist educators, parents, students, government officials, and policymakers in making proper decisions on the effective use of AI and inclusion.